Optimization Criteria of Power Transformer Operation - A. A. Gonchar (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
It has been shown that minimum losses in active power of a power transformer do not correspond to its maximum efficiency. For a transformer being operated there are no so called «zones of its economical operation». In this case strictly specified value of active power losses corresponds to a particular current of the winding.